Prognostic Significance and Immuno-Histochemical Expression of Vascular Endothelial Growth Factor in Canine Cutaneous Tumours - Kumar, Veluchamy; Hemalatha, Senthilnayagam; Balachandran, Chidhambaram; Thangathurai, Ramasamy (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Vascular endothelial growth factor (VEGF) is the most thoroughly investigated in human oncology. It is the major angiogenic factor involved in physiological as well as pathological angiogenesis. Especially, in canine oncology vascular endothelial growth factor was a useful additional criterion for evaluating malignancy and growth potential in some tumours. But this angiogenic factor was still poorly investigated in veterinary oncology. The present work was undertaken to evaluate the expression of vascular endothelial growth factor in the prognosis of cutaneous tumours in dogs. 103 Fine needle aspiration cytology samples were collected from Madras Veterinary College, Teaching Hospital, Chennai. VEGF expression was analyzed by immunohistochemistry on formalin fixed paraffin embedded sections of selected 28 canine cutaneous tumours. The VEGF immune expression was noticed in all types of cutaneous tumours in dogs.  But the VEGF expression was more in all malignant tumours when compared to the benign tumours. Among the malignant tumours, metastasis and death cases showed higher expression. Besides, the tumours which showed high expression of VEGF showed higher malignant features than their counterparts. Thus, the study showed that there was prognostic significance in assessing tumour angiogenesis by independent VEGF expression in canine cutaneous tumours.
Keywords: Canine; Cutaneous tumours; Histopathology; Immunohistochemistry; VEGF expression